Peran Koperasi dalam Rangka Pemberdayaan Ekonomi Masyarakat Terpapar Pada Kawasan Rawan Bencana di Wilayah Kabupaten Tuban - Sholichah, Nihayatus; Paidjala, Mesak (Prodi Sosiologi Agama, 2017)
As one of the populist economy institutes in Indonesia, cooperatives have grown and developed almost the most of territory in Indonesia. No exception is the probability there are also many cooperatives within the disaster-prone territories or regions. So that the existence of cooperatives in disaster-prone areas will be the pedestal and hope of local society to come into play and help quickly to give stimulant recovery and society economy empowerment, at the moment when the societies get disaster. A Cooperative is one of the institutes that can participate together with society in disaster risk management. As an institute that is established together and based on kinship, cooperatives are hoped to be the nearest institute to citizens so that can result in the best solutions to overcome disaster problems. Various manners can be done cooperatively to help society to decrease the disaster impact; one of them is to prepare reserve stock for emergency needs. Because of still in a region that is prone to disaster, the stocks should be stored in a safe place. These reserve stocks can be taken from SHU (effort remaining results) and appropriated to the agreement so that they can be given freely while waiting for help from outsiders. So in the other words cooperatives have the function of the provider of emergency needs after a disaster so the needs of victims (the societies around the cooperative) can be fulfilled quickly.